Domination and misframing in the refugee regime. Issue 7 (10th November 2022) - Draper, Jamie
ABSTRACT: The current practices of refugee protection refugees largely leave the burdens of the refugee regime to lie where they fall. Those states which are geographically proximate to refugee-producing regions, already amongst the least advantaged, bear the bulk of these burdens. In this paper, I critically assess two proposals which seek to address this maldistribution: a market in asylum services and a principle of comparative advantage. I argue that from the standpoint of justice, these proposals share two objectionable features. First, they enable relations of domination between states, because they ignore the background relations of inequality upon which they depend for their effectiveness. Second, they institute an injustice of 'misframing, ' in that they preclude consideration of refugees' legitimate claims to be hosted (or not to be hosted) in a particular state. The failings of these approaches are illuminating and, I argue, provide us with some theoretical desiderata for a positive account of justice in the distribution of responsibilities to refugees.